Positive electrode active material, method for preparing the same, and rechargeable lithium battery

CN122992017APending Publication Date: 2026-10-27SAMSUNG SDI CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610540982.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2026-04-15
Filing Date
2026-04-22
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

[0010]根据一些实例实施方式的用于制备正电极活性物质的方法可在使制造成本降低或最小化的同时提供具有期望的或改善的导电性的正电极活性物质。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992017A_ABST
    Figure CN122992017A_ABST
Patent Text Reader

Abstract

Provided are a positive electrode active material, a method for producing the same, and a rechargeable lithium battery. The positive electrode active material includes: core particles including a lithium cobalt-based complex oxide; and a carbon coating layer on a surface of the core particles. The carbon coating layer includes carbon nanotubes and graphene having a layered structure in a range of 2 layers to 50 layers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The positive electrode active material, its preparation method, and rechargeable lithium battery are disclosed. Background Technology

[0002] Portable information devices such as cellular phones, laptops, and smartphones typically use rechargeable lithium batteries with high energy density and portability as their power source. Recently, rechargeable lithium batteries with high energy density have proven advantageous as a power source or energy storage source for hybrid or electric vehicles.

[0003] Various positive electrode active materials exist to realize rechargeable lithium batteries for the above applications. For example, lithium nickel-based oxides, lithium nickel manganese cobalt composite oxides, lithium nickel cobalt aluminum composite oxides, and lithium cobalt oxides are mainly used as positive electrode active materials.

[0004] With increasing research into positive electrode active materials with desired or improved properties such as conductivity and density, it is advantageous to develop positive electrode active materials exhibiting high conductivity and density. Summary of the Invention

[0005] Some exemplary implementations include positive electrode active materials capable of improving conductivity and density, methods for preparing said positive electrode active materials, and rechargeable lithium batteries.

[0006] In some exemplary embodiments, the positive electrode active material includes: a core particle comprising a lithium cobalt-based composite oxide; and a carbon coating layer (coating) on ​​the surface of the core particle. The carbon coating layer includes carbon nanotubes and graphene having a layered structure ranging from 2 to 50 layers.

[0007] In some exemplary embodiments, the method for preparing the positive electrode active material includes: (i) preparing (preparing) core particles comprising a lithium cobalt-based composite oxide, and (ii) having an average size (D) in the range of about 3 μm to about 25 μm. 50 Flake-like graphite was pulverized to prepare a sample with an average size (D) of less than or equal to about 2.5 μm. 50 (iii) the use of microparticle graphite (microparticle graphite) and the use of dry mixing of core particles, microparticle graphite and carbon nanotubes (dry mixing) to obtain a positive electrode active material.

[0008] In some implementations, the rechargeable lithium battery includes a positive electrode, a negative electrode, and an electrolyte. The positive electrode includes a current collector and a layer of positive electrode active material on the current collector, the layer of positive electrode active material including the positive electrode active material.

[0009] The positive electrode active material according to some exemplary embodiments can exhibit high agglomerate (disc) density and low powder resistance, and can have improved conductivity. Furthermore, a positive electrode including the aforementioned positive electrode active material and a rechargeable lithium battery can have improved capacity and energy density.

[0010] The method for preparing a positive electrode active material according to some example embodiments can provide a positive electrode active material with desired or improved conductivity while reducing or minimizing manufacturing costs. Attached Figure Description

[0011] Figures 1 to 4 A cross-sectional view of a rechargeable lithium battery according to some exemplary embodiments is shown schematically.

[0012] Figure 5 This is a scanning electron microscope image of the surface of the positive electrode active material prepared in Example 1.

[0013] Figure 6 This is a transmission electron microscope image of the cross-section of the positive electrode active material prepared in Example 1. Detailed Implementation

[0014] In the following detailed description of exemplary embodiments, those skilled in the art will readily recognize them. However, this disclosure may be embodied in many different forms and is not to be construed as limited to the exemplary embodiments set forth herein.

[0015] The terminology used herein is for describing exemplary implementations only and is not intended to limit the scope of this disclosure. Unless the context clearly requires otherwise, singular expressions include plural expressions.

[0016] "The combination of its components" means mixtures, laminates, complexes, copolymers, alloys, blends, reaction products, etc.

[0017] It should be understood that terms such as “comprising,” “including,” or “having” are intended to indicate the presence of the features, quantities, steps, elements, or combinations thereof embodied, but do not preclude the possibility of the presence or addition of one or more other features, quantities, steps, elements, or combinations thereof.

[0018] In the accompanying drawings, for clarity, the thickness of layers, films, panels, regions, etc., may be exaggerated, and the same reference numerals denote the same elements throughout the specification. It should be understood that when an element, such as a layer, film, region, or substrate, is referred to as being "on" another element, the element may be directly on the other element, or there may be intermediate elements therein. Conversely, when an element is referred to as being "directly on" another element, there are no intermediate elements.

[0019] The term "layer" in this article includes not only the shape that forms across the entire surface when viewed from a plan view, but also the shape that forms on a portion of the surface.

[0020] The average particle size can be measured by methods known to those skilled in the art, such as by a particle size analyzer or by transmission electron microscopy (TEM) or scanning electron microscopy (SEM) images. Alternatively, the average particle size value can be obtained by measuring using a dynamic light scattering method, performing data analysis, counting the number of particles for each particle size range, and calculating the average particle size value based on the count. As used herein, unless otherwise defined, the average particle size (D...) 50 The mean particle size (D) can mean the diameter of particles that have a cumulative volume of 50% in the particle size distribution. As used herein, unless otherwise defined, the mean particle size (D) 50 This means the diameter of particles that have a cumulative volume of 50% in a particle size distribution obtained by randomly measuring the size (diameter or length of the major axis) of about 20 particles in a scanning electron microscope image.

[0021] "Or" will not be interpreted as exclusive; for example, "A or B" will be interpreted as including A, B, A+B, etc.

[0022] The term "metal" is interpreted as encompassing common metals, transition metals, and metalloids (semi-metals).

[0023] When the terms “about” or “substantially” are used in this specification with respect to numerical values, it is intended that the relevant numerical values ​​include a tolerance of ±10% around the stated value. When a range is specified, the range includes all values ​​within that range, such as an increment of 0.1%.

[0024] Positive electrode active material

[0025] Positive electrode active materials according to some exemplary embodiments include: core particles comprising lithium cobalt-based composite oxides and a carbon coating layer on the surface of the core particles, wherein the carbon coating layer comprises carbon nanotubes and graphene having a layered structure in the range of 2 to 50 layers.

[0026] Typically, during the manufacturing of the positive electrode, binders and conductive materials are added to improve the adhesion strength between the electrode plate and the positive electrode active material, as well as the conductivity of the positive electrode. However, with the increase in the amount of binder and conductive material used, the following challenge arises: the energy density of the battery decreases because the amount of positive electrode active material decreases. Since the positive electrode active material according to some exemplary embodiments includes a carbon coating layer (the carbon coating layer includes carbon nanotubes and graphene with a layered structure ranging from 2 to 50 layers), even with a small amount of carbon material, the carbon coating layer can be coated (applied) onto the surface of the active material particles (core particles), thereby enhancing adhesion strength and conductivity. Therefore, even with the use of a small amount of binder and conductive material during the manufacturing of the positive electrode, high energy density and conductivity can be ensured. Furthermore, as the amount of binder and conductive material used in the manufacturing of the positive electrode decreases, the amount of positive electrode active material can increase, allowing rechargeable lithium batteries including the positive electrode active material to exhibit high capacity and high energy density characteristics.

[0027] When using crystalline carbon materials with low dispersion to form carbon coatings, uniformly forming the carbon coating on the surface of the core particles can be challenging due to the agglomeration of the carbon materials. However, according to some exemplary embodiments, the positive electrode active material can exhibit a carbon coating with a thin and uniform or substantially uniform thickness by selecting a crystalline carbon material as the source material (source material) and coating it under appropriate or desired conditions. The carbon coating has a layered structure exhibiting a dense crystalline structure and can comprise crystalline carbon formed in a two-dimensional plane on the surface of the core particles. Therefore, the resistance of the positive electrode active material is reduced, the agglomeration density is improved, lithium-ion insertion and extraction can proceed more efficiently, and ionic conductivity is improved because lithium ions diffuse along the layered structure. Furthermore, positive electrodes including positive electrode active materials exhibit desired or improved electronic conductivity, even if they do not contain a single conductive material or contain a substantially small amount of conductive material (even when the positive electrode does not contain a single conductive material or contains a substantially small amount of conductive material), and positive electrodes including such positive electrode active materials can exhibit high electrode plate adhesion strength, even if they contain a substantially small amount of binder (even when they contain a substantially small amount of binder). Rechargeable lithium batteries including such positive electrodes can exhibit high capacity and energy density, and can improve overall electrochemical performance such as charge / discharge efficiency and rate characteristics.

[0028] Methods for inducing a carbon coating layer including graphene on the surface of the core particles of positive electrode active materials using graphene as a raw material have been proposed. However, the coating process is complex or costly, thus limiting commercialization, and there are also limitations in ensuring a carbon coating layer with a uniform or substantially uniform thickness on the surface of the core particles. Furthermore, techniques for coating amorphous carbon on the surface of core particles have been proposed, but uniform coating can be challenging, and there are limitations in increasing energy density while simultaneously increasing the electronic conductivity and reducing the resistance of the positive electrode. Positive electrode active materials according to some exemplary embodiments have successfully introduced graphene as a carbon coating layer on the surface of the core particles in the form of a uniform or substantially uniform film with a thickness of 2 to 50 atomic layers or a few nanometers to tens of nanometers. Compared to coating amorphous carbon or other crystalline carbons, positive electrode active materials according to some exemplary embodiments exhibit higher electronic and ionic conductivity, can increase energy density while reducing resistance, and can exhibit improved electrochemical performance. Furthermore, according to some exemplary embodiments, the positive electrode active material can be applied using a dry coating method while using graphite as a low-cost material, thus reducing costs, exhibiting good processability, and being advantageous for large-scale production.

[0029] Furthermore, because the carbon coating layer of the positive electrode active material, according to some exemplary embodiments, also includes carbon nanotubes in addition to graphene, the agglomeration density of the positive electrode active material is further improved, and thus the energy density of the rechargeable lithium battery including such a positive electrode active material can also be improved or maximized. For example, due to the lubricating properties of carbon materials as the source material of the carbon coating layer, a large amount of carbon coating layer is uniformly or substantially uniformly provided on the surface of the core particles, thereby improving or maximizing the agglomeration density of the positive electrode active material. At the same time, when the carbon coating layer includes both graphene and carbon nanotubes, the powder resistance of the positive electrode active material is further reduced, thereby improving or maximizing the electrical conductivity (conductivity) of the positive electrode active material.

[0030] For example, carbon nanotubes, as a source material for carbon coatings, can increase electronic conductivity even in substantially small amounts. However, because uniformly coating the surface of the core particles is challenging, the coating properties can be poor, such as uneven coating, aggregation on the surface, or separation from the surface. Therefore, when carbon nanotubes are coated solely on the surface of the core particles, powder resistance can increase, leading to a decrease in electronic conductivity and particle density. Additionally, when graphene is coated solely on the surface of the core particles, the graphene is coated in a sheet-like shape on the positive electrode active material particles, thereby increasing lubrication properties, reducing powder resistance, and increasing particle density, but there are limitations in increasing electronic conductivity. However, according to some exemplary embodiments, the positive electrode active material in the carbon coating includes carbon nanotubes in addition to graphene, and when graphene is coated in a sheet-like shape on the surface of the core particles, the carbon nanotubes can be firmly adhered within the sheet or to the surface of the sheet. That is, because graphene and carbon nanotubes can be uniformly or substantially uniformly coated on the surface of the core particles simultaneously or concurrently, the positive electrode active material can acquire lubricating properties while improving or maximizing electronic conductivity.

[0031] The following describes in detail the preparation of the positive electrode active material according to some example embodiments.

[0032] Core Particles

[0033] The core particles comprise lithium-cobalt-based composite oxides. For example, the core particles may comprise lithium-cobalt-based composite oxides represented by Chemical Formula 1:

[0034] Chemical Formula 1:

[0035] Li a1 Co x1 M 1 y1 O 2-b1 X b1 .

[0036] In chemical formula 1, 0.9 ≤ a1 ≤ 1.8, 0.7 ≤ x1 ≤ 1, 0 ≤ y1 ≤ 0.3, 0.9 ≤ x1 + y1 ≤ 1.1, and 0 ≤ b1 ≤ 0.1, M 1 X is or includes one or more elements of Al, B, Ba, Ca, Ce, Cr, Cu, Fe, Mg, Mn, Mo, Ni, Se, Si, Sn, Sr, Ti, V, W, Y, Zn, and Zr, and X is or includes one or more elements of F, P, and S.

[0037] When the core particles include lithium cobalt-based composite oxides represented by chemical formula 1, high-voltage designs for rechargeable lithium batteries are possible, and the reliability and safety of rechargeable lithium batteries can be improved due to reduced gas generation at high voltages. Furthermore, battery resistance can be reduced or suppressed by leveraging synergistic effects in fast-charging systems.

[0038] The average particle size (D) of the core particles 50 The core particle size can range from about 1 μm to about 25 μm, from about 3 μm to about 22 μm, or from about 10 μm to about 18 μm. If the average particle size (D) of the core particles... 50 The above range must be met (when the average particle size of the core particles (D) is within the range). 50 When the above ranges are met, the structural stability of the positive electrode active material can be improved while simultaneously enhancing its electrical conductivity and particle density. Furthermore, the stability of the positive electrode slurry and the density of the electrode plate mixture (mixing density) in the positive electrode manufacturing process can be improved. Additionally, since the movement path of lithium ions to the surface of the positive electrode active material becomes longer, the formation of impurities on the surface of the positive electrode active material can be reduced or minimized. Therefore, problems that may occur due to surface impurities, such as reduced battery capacity, increased interface resistance due to interference with lithium ion movement, gas generation due to impurity decomposition, and consequently, battery expansion, can be reduced or prevented. As a result, the capacity characteristics, high-temperature stability, and charge / discharge characteristics of rechargeable lithium batteries including the aforementioned positive electrode active material can be improved. In this paper, the average particle size (D) of the core particles is... 50 The particle size distribution can be obtained by randomly selecting about 20 particles from the scanning electron microscope image of the core particles, measuring their particle size (diameter, major axis, or major axis length) to obtain the particle size distribution, and then taking the size of the particles with a cumulative volume of 50% of the particle size distribution as the average particle size.

[0039] Core particles may include an average particle size (D) in the range of about 8 μm to about 20 μm. 50 The first particle and having an average particle size (D) in the range of about 0.5 μm to about 6 μm. 50 The first particle, with a relatively large average particle size, can be considered a large particle, and the second particle, with a relatively small average particle size, can be considered a small particle. Because the positive electrode active material layer includes both large and small particles, capacity and energy density can be improved or maximized, and long cycle life characteristics can be exhibited.

[0040] The average particle size of the first particle (D) 50The particle size can range from about 9 μm to about 20 μm, from about 10 μm to about 18 μm, or from about 12 μm to about 16 μm. In this paper, the average particle size (D) of the first particle is... 50 The particle size distribution can be obtained by randomly selecting about 20 particles from the scanning electron microscope (SEM) image of the first particle, measuring the particle size (diameter, major axis, or length of the major axis) to obtain the particle size distribution, and then taking the size of the particles with a cumulative volume of 50% of the particle size distribution as the average particle size.

[0041] The average particle size of the second particle (D) 50 The particle size can range from about 0.8 μm to about 6 μm, from about 1.0 μm to about 5.8 μm, or from about 1.0 μm to about 5.5 μm. In this paper, the average particle size (D) of the second particle is... 50 The average particle size (D) can be obtained through the following methods. 50 ): Approximately 20 particles were randomly selected from the scanning electron microscope (SEM) image of the second particle, and the particle size (diameter, major axis, or length of major axis) was measured to obtain the particle size distribution. The size of the particles with a cumulative volume of 50% of the particle size distribution was then taken as the average particle size.

[0042] carbon coating

[0043] A carbon coating layer is disposed on the surface of the core particle and includes carbon nanotubes and graphene having a layered structure ranging from 2 to 50 layers. Through this carbon coating layer, conductivity and adhesion strength to the electrode plate are ensured even when small amounts of binder and conductive material are used during the manufacture of the positive electrode. Furthermore, as the amount of binder or conductive material used during the manufacture of the positive electrode decreases, the amount of positive electrode active material can be increased, allowing the rechargeable lithium battery to exhibit high capacity and high energy density characteristics. For example, the carbon coating layer comprises crystalline carbon formed in a two-dimensional plane on the surface of the core particle and can have a thin and uniform or substantially uniform thickness. Furthermore, the graphene in the carbon coating layer can have a layered structure exhibiting a dense crystalline structure. Therefore, the electronic conductivity of the positive electrode active material is improved and the interfacial resistance can be reduced, lithium-ion insertion and extraction can proceed more efficiently, and ionic conductivity is improved because lithium ions diffuse along the layered structure.

[0044] Furthermore, because the carbon coating layer includes carbon nanotubes along with graphene, the electrical conductivity and particle density of the positive electrode active material can be further improved through the synergistic effect of graphene and carbon nanotubes. For example, even with very low or substantially low amounts of graphene and carbon nanotubes, the capacity and energy density of the rechargeable lithium battery can be improved while ensuring the conductivity of the positive electrode and adhesion to the electrode plate. For example, when the carbon coating layer includes both graphene and carbon nanotubes, higher electrical conductivity and particle density can be achieved with lower amounts compared to using graphene or carbon nanotubes alone. For example, when graphene is coated on the surface of the core particle in a sheet shape, carbon nanotubes can adhere firmly to the sheet or to the surface of the sheet. That is, because graphene and carbon nanotubes can be uniformly or substantially uniformly coated on the surface of the core particle simultaneously or concurrently, the positive electrode active material can acquire lubricating properties while improving or maximizing electronic conductivity.

[0045] For example, graphene and carbon nanotubes can be combined (bonded) to each other and exist on a single sheet plane. As another example, when graphene is coated on the surface of the core particle in a sheet shape, carbon nanotubes in the form of fibers can be disposed on the graphene sheet. As another example, the positive electrode active material may include a first coating layer and a second coating layer, the first coating layer being disposed on the surface of the core particle and comprising graphene having a layered structure in the range of 2 to 50 layers, and the second coating layer being disposed on the first coating layer and comprising carbon nanotubes.

[0046] Layered structures ranging from 2 to 50 layers can be represented as layered structures of 2 to 50 atomic layers. As examples, the carbon coating layer can comprise graphene with layered structures of 2 to 48 layers, 5 to 45 layers, 7 to 40 layers, or 10 to 35 layers. The number of layers in the layered structure can be measured in high-resolution transmission electron microscopy (HR-TEM) images of the positive electrode active material particles.

[0047] The interlayer spacing (d) of the layered structure 002 The interlayer spacing (d) can be in the range of about 0.320 nm to about 0.350 nm, for example, about 0.325 nm to about 0.348 nm, about 0.328 nm to about 0.345 nm, or about 0.330 nm to about 0.342 nm. 002 The above range is satisfied (when the interlayer spacing (d) of the layered structure is satisfied). 002 When the above ranges are met, the particle density and conductivity of the positive electrode active material can be further improved. In this paper, the interlayer spacing (d) 002 ) can be measured using methods known to those skilled in the art. For example, the interlayer spacing (d) of a layered structure 002The peaks on the (002) plane can be obtained by X-ray diffraction (XRD) of the carbon coating layer, and then analyzed. In this paper, the (002) plane represents the range of 25.0° < 2θ < 27.0°, where 2θ represents the diffraction angle. For example, conventional procedures equipped in XRD equipment can be used as data processing and analysis procedures to subject the XRD measurement data to noise removal (baseline setting), etc. In addition, the peak profiles on the (002) plane can be fitted using conventional fitting functions such as Gaussian functions, Lorentz functions, etc. For example, the interlayer spacing (d) of the layered structure 002 This can be achieved by measuring the interlayer spacing (d) of microparticle graphite. 002 The method is used to represent the interlayer spacing (d) of particulate graphite. 002 The number of layers and the interlayer spacing (d) in a layered structure can be measured by XRD analysis of particulate graphite. 002 The thickness of the coating layer and the total thickness of the coating layer were determined as average values, obtained by measurements at multiple randomly selected locations on the cross-section of the core particle via HR-TEM. Note that the relationships between these parameters follow the physical properties of the graphene coating layer, where the total thickness of the coating layer is the product of the number of layers and the average interlayer spacing.

[0048] Graphene may have a Raman spectrum in the range of about 0.15 to about 0.50, and for example about 0.15 to about 0.45, about 0.18 to about 0.45, or about 0.20 to about 0.40 at 1350 cm⁻¹. -1 Nearby peak intensity (I) D ) at 1580 cm -1 Nearby peak intensity (I) G The ratio of (I) D / I G If graphene's I... D / I G The value satisfies the above range (when the I of graphene) D / I G When the values ​​meet the above range, the particle density and conductivity of the positive electrode active material can be improved or maximized. For example, Raman spectroscopy can be performed using a Raman spectrometer (e.g., ICRM7000 (Renishaw), etc.) at a laser wavelength of approximately 632 nm and a wavelength of approximately 946 cm⁻¹. -1 The lowest Raman shift was measured. The peak intensity ratio described in this paper was obtained from approximately 946 cm⁻¹. -1 The peaks observed within the Raman shift range starting from the lowest Raman shift are obtained. These measurement conditions are standard in the art and will be within the capabilities of those skilled in the art as follows: adjusting these parameters, such as laser (laser) power or exposure time, while maintaining a relative trend in the peak intensity ratio to ensure reproducibility.

[0049] The thickness of graphene can be less than or equal to about 20 nm, and the size of graphene can be less than or equal to about 2.5 μm. For example, the thickness of graphene can be less than or equal to about 19 nm, less than or equal to about 18 nm, less than or equal to about 17 nm, less than or equal to about 16 nm, or less than or equal to about 15 nm, and can be greater than or equal to about 1 nm, greater than or equal to about 2 nm, greater than or equal to about 3 nm, greater than or equal to about 4 nm, or greater than or equal to about 5 nm. If the thickness of graphene meets the above ranges (when the thickness of graphene meets the above ranges), the positive electrode active material can further improve the agglomeration density and conductivity. In this paper, the thickness of graphene can be measured by Raman spectroscopy. For example, it can be based on the Raman spectrum at 1580 cm⁻¹. -1 The peak intensity near 2700 cm⁻¹ -1 The thickness of graphene is measured by the ratio of the intensities of nearby peaks. However, this disclosure is not limited to this, and the thickness of graphene can be measured by, for example, transmission electron microscopy (TEM), scanning electron microscopy (SEM), atomic force microscopy (AFM), time-of-flight secondary ion mass spectrometry (TOF-SIMS), X-ray photoelectron spectroscopy (XPS), or energy-dispersive spectroscopy (EDS).

[0050] For example, the size of graphene can be less than or equal to about 1.5 μm, less than or equal to about 1.0 μm, less than or equal to about 1.0 μm, or less than or equal to about 0.5 μm, and can be greater than or equal to about 0.01 μm, greater than or equal to about 0.05 μm, or greater than or equal to about 0.08 μm. If the size of graphene meets the above ranges (when the size of graphene meets the above ranges), the positive electrode active material can further improve the agglomerate density and conductivity. In this paper, regarding the size of graphene, because graphene is sheet-shaped, it means the longest length or the length of the long axis in the portion corresponding to the surface of the sheet, rather than the thickness of the sheet. The size of graphene can also mean the longest length in the line connecting one point on one surface of the graphene sheet to another point. For example, the size of graphene can be measured by TEM, SEM, AFM, TOF-SIMS, XPS, or EDS analysis.

[0051] The carbon-coated graphene can be derived from particulate graphite with an average size of less than or equal to about 2.5 μm. In this case, a carbon coating layer of uniform or substantially uniform thickness can be formed on the surface of the core particles, and thus, the positive electrode active material can have improved or maximized aggregate density and conductivity. In addition, the structural stability of the positive electrode active material can be improved, side reactions with the electrolyte can be effectively reduced or suppressed, gas generation under high voltage and high temperature conditions can be reduced, and long cycle life characteristics can be exhibited.

[0052] Particulate graphite may be or include tabular particles. The average size (D) of particulate graphite 50 The average size of the particulate graphite can be less than or equal to about 2.5 μm, for example, less than or equal to about 1.5 μm, less than or equal to about 1.0 μm, less than about 1 μm, or less than or equal to about 0.5 μm, and can be greater than or equal to about 0.01 μm, greater than or equal to about 0.05 μm, or greater than or equal to about 0.08 μm. If the average size of the particulate graphite meets the above range (when the average size of the particulate graphite meets the above range), a carbon coating layer of uniform or substantially uniform thickness can be formed on the surface of the core particles, and the positive electrode active material can have improved or maximized agglomerate density and conductivity. In this paper, the average size of the particulate graphite (D...) 50 Particle size can be measured using a particle size analyzer and refers to the size of particles that have a cumulative volume of 50% in the particle size distribution. Additionally, particle size can be expressed as the length of the longest axis in a plane perpendicular to the thickness direction within a plate shape.

[0053] The thickness of the particulate graphite can be less than or equal to about 1.0 μm, and for example, it can be less than about 1 μm, less than or equal to about 0.9 μm, less than or equal to about 0.7 μm, or less than or equal to about 0.5 μm, and can be greater than or equal to about 0.01 μm, greater than or equal to about 0.05 μm, or greater than or equal to about 0.08 μm. If the thickness of the particulate graphite meets the above ranges (when the thickness of the particulate graphite meets the above ranges), a carbon coating layer of uniform or substantially uniform thickness can be formed on the surface of the core particles, and the positive electrode active material can have improved or maximized agglomerate density and conductivity. In this document, the thickness of the particulate graphite can be measured by transmission electron microscopy of the particulate graphite. Alternatively, the thickness of the particulate graphite can be measured by transmission electron microscopy of a cross-section of particulate graphite particles cut by focused ion beam (FIB). However, this disclosure is not limited thereto, and the thickness of the particulate graphite can be measured by, for example, SEM, TEM, TOF-SIMS, XPS, AFM or EDS analysis, and can be measured by TEM-EDS line profile.

[0054] Particulate graphite may have a Raman spectroscopy value in the range of about 0.15 to about 0.50, for example about 0.15 to about 0.45, about 0.18 to about 0.45, or about 0.20 to about 0.40 at 1350 cm⁻¹. -1 Nearby peak intensity (I) D ) at 1580 cm -1 Nearby peak intensity (I) G The ratio of (I) D / I G If the I of particulate graphite D / I G The value satisfies the above range (when the I of particulate graphite) D / I G When the value meets the above range, a carbon coating layer with a uniform or substantially uniform thickness can be formed on the surface of the core particles, and the particle density and conductivity of the positive electrode active material can be improved or maximized.

[0055] Based on the total weight of 100% positive electrode active material, the amount of graphene included in the carbon coating can range from about 0.02% to about 3.0% by weight, for example, from about 0.02% to about 2.8% by weight, from about 0.03% to about 2.5% by weight, from about 0.05% to about 2.0% by weight, from about 0.05% to about 1.0% by weight, from about 0.05% to about 0.5% by weight, or from about 0.05% to about 0.8% by weight. If the amount of graphene meets the above range (when the amount of graphene meets the above range), the particle density and conductivity of the positive electrode active material can be ensured, while improving the high capacity and high energy density characteristics of the rechargeable lithium battery. For example, even if the amount of graphene is substantially small, less than about 1% by weight (even when the amount of graphene is substantially small, less than about 1% by weight), graphene can still coat the surface of the core particles, thereby increasing the electrical conductivity of the positive electrode active material, increasing the particle density, and increasing the density of the positive electrode.

[0056] Carbon nanotubes may include at least one of single-walled carbon nanotubes (SWCNTs), thin-walled carbon nanotubes (TWCNTs), and multi-walled carbon nanotubes (MWCNTs).

[0057] The average length of carbon nanotubes can range from about 0.1 μm to about 35 μm, for example, about 0.3 μm to about 30 μm, about 0.5 μm to about 25 μm, about 1 μm to about 20 μm, about 3 μm to about 18 μm, or about 5 μm to about 15 μm. If the average length of the carbon nanotubes meets the above range (when the average length of the carbon nanotubes meets the above range), a carbon coating layer of uniform or substantially uniform thickness can be formed on the surface of the core particle, and the positive electrode active material can have improved or maximized aggregate density and conductivity. In this paper, the length of the carbon nanotube refers to the length of the long axis passing through the center of the carbon nanotube unit. For example, the average length of the carbon nanotubes can be obtained by randomly selecting about 20 carbon nanotubes from the results of SEM observation, measuring their lengths, and averaging them by calculation.

[0058] The average diameter of carbon nanotubes can range from about 1 nm to about 50 nm, for example, from about 1 nm to about 40 nm, from about 1.5 nm to about 30 nm, from about 1.8 nm to about 20 nm, or from about 2 nm to about 15 nm. In this paper, the diameter of a carbon nanotube means the length of its minor axis, which passes through the center of the carbon nanotube unit and is perpendicular to its major axis. For example, the average diameter of a carbon nanotube can be obtained by randomly selecting about 20 carbon nanotubes from TEM observations, measuring their diameters, and then calculating the average value.

[0059] Based on the total weight of 100% positive electrode active material, the amount of carbon nanotubes including the carbon coating can range from about 0.02% to about 3.0% by weight, for example, from about 0.02% to about 2.8% by weight, from about 0.03% to about 2.5% by weight, from about 0.05% to about 2.0% by weight, from about 0.05% to about 1.0% by weight, from about 0.05% to about 0.5% by weight, or from about 0.05% to about 0.8% by weight. If the amount of carbon nanotubes meets the above range (when the amount of carbon nanotubes meets the above range), the particle density and conductivity of the positive electrode active material can be ensured, while improving the high capacity and high energy density characteristics of the rechargeable lithium battery. For example, even if the amount of carbon nanotubes is substantially small, less than about 1% by weight (even when the amount of carbon nanotubes is substantially small, less than about 1% by weight), carbon nanotubes can increase the electrical conductivity of the positive electrode active material, increase the particle density, and increase the density of the positive electrode.

[0060] For example, the carbon coating can be in the form of a film that continuously or substantially continuously surrounds the surface of the core particle, or it can be in the form of a shell that surrounds the entire surface of the core particle. This differs from structures where only a portion of the surface of the core particle is partially coated. When the carbon coating is formed to completely surround the surface of the core particle, the agglomeration density and conductivity of the positive electrode active material can be improved or maximized. Furthermore, it can improve the electrode plate adhesion strength of the positive electrode active material, without increasing resistance or decreasing capacity, improve structural stability, effectively reduce or suppress side reactions with the electrolyte, reduce gas generation under high voltage and high temperature conditions, and exhibit long-life characteristics.

[0061] The thickness of the carbon coating can be in the range of about 3 nm to about 50 nm, and for example, about 3 nm to about 45 nm, about 3 nm to about 40 nm, about 3 nm to about 35 nm, about 3 nm to about 30 nm, about 4 nm to about 20 nm, or about 5 nm to about 15 nm. If the thickness of the carbon coating meets the above ranges (when the thickness of the carbon coating meets the above ranges), the structural stability of the positive electrode active material can be improved, and side reactions with the electrolyte can be effectively reduced or suppressed without increasing resistance or decreasing capacity due to the carbon coating. For example, the thickness of the carbon coating can be measured by transmission electron microscopy of the cross-section of the positive electrode active material particles cut by FIB. However, this disclosure is not limited thereto, and the thickness of the carbon coating can be measured by, for example, SEM, AFM, TOF-SIMS, XPS, or EDS analysis, and can be measured by TEM-EDS line profiling.

[0062] As an example, the carbon coating layer can have a uniform or substantially uniform thickness, while also being thin at the level of a few nanometers to tens of nanometers. For example, the difference between the highest and lowest thicknesses of the carbon coating layer can be less than or equal to about 30 nm, such as less than or equal to about 25 nm, less than or equal to about 20 nm, or less than or equal to about 15 nm, and can be greater than or equal to about 0.30 nm, greater than or equal to about 0.33 nm, greater than or equal to about 0.35 nm, or greater than or equal to about 0.40 nm. The fact that the difference between the highest and lowest thicknesses of the carbon coating layer meets the above ranges means that a carbon coating layer of uniform or substantially uniform thickness can be formed in the form of a film on the surface of the positive electrode active material particles, and therefore, the aggregate density and conductivity of the positive electrode active material can be improved or maximized. In this paper, the highest and lowest thicknesses of the carbon coating layer can be measured based on electron microscopy images of the positive electrode active material. For example, in an electron microscope image of the cross-section of a positive electrode active material particle, the thickness of the thickest part of the carbon coating can be defined as the maximum thickness of the carbon coating, and the thickness of the thinnest part can be defined as the minimum thickness of the carbon coating. The thickness of the carbon coating can be the vertical distance from the outer surface of the core particle to the outer surface of the carbon coating. For example, a scanning electron microscope or a transmission electron microscope can be used as the electron microscope.

[0063] The particle density of the positive electrode active material can be greater than or equal to approximately 4.35 g / cm³. 3 Furthermore, the powder resistivity of the positive electrode active material can be less than or equal to approximately 10,000 Ω·cm. For example, the particle density of the positive electrode active material can be greater than or equal to approximately 4.355 g / cm³. 3 ≥4.36 g / cm³ 3 Greater than or equal to approximately 4.365 g / cm³ 3 Or greater than or equal to approximately 4.37 g / cm³ 3 And it can be less than or equal to about 20 g / cm³ 3 Less than or equal to approximately 18 g / cm³ 3 Less than or equal to approximately 15 g / cm³ 3 Less than or equal to approximately 10 g / cm³ 3 Or less than or equal to approximately 8 g / cm³ 3If the agglomerate density of the positive electrode active material meets the above range (when the agglomerate density of the positive electrode active material meets the above range), the density of the positive electrode can be improved, and the electrochemical properties of the rechargeable lithium battery, such as capacity, initial efficiency, and cycle life characteristics, can be improved. In this paper, agglomerate density refers to the density measured by pressing the positive electrode active material under a certain pressure. For example, agglomerate density refers to the density measured for agglomerates formed by pressing the positive electrode active material under a pressure of approximately 9 tons for approximately 30 seconds.

[0064] For example, the powder resistivity of the positive electrode active material may be less than or equal to about 9,000 Ω·cm, less than or equal to about 8,000 Ω·cm, less than or equal to about 7,000 Ω·cm, less than or equal to about 6,000 Ω·cm, less than or equal to about 5,000 Ω·cm, less than or equal to about 4,000 Ω·cm, less than or equal to about 3,000 Ω·cm, or less than or equal to about 2,000 Ω·cm, and may be greater than or equal to about 50 Ω·cm, greater than or equal to about 100 Ω·cm, greater than or equal to about 150 Ω·cm, greater than or equal to about 200 Ω·cm, greater than or equal to about 500 Ω·cm, greater than or equal to about 1,000 Ω·cm, greater than or equal to about 1,500 Ω·cm, or greater than or equal to about 1,800 Ω·cm. The fact that the powder resistance of the positive electrode active material meets the above range means that it exhibits the desired conductivity of the positive electrode active material, and thus improves the electrochemical characteristics of the rechargeable lithium battery, such as capacity, initial efficiency, and cycle life. For example, the powder resistance of the positive electrode active material can be measured using a powder ohmmeter and can be represented by the powder resistance measured at 20 kN by applying pressure from about 0 kN to about 20 kN to the positive electrode active material particles.

[0065] Method for preparing positive electrode active materials

[0066] A method for preparing a positive electrode active material according to some exemplary embodiments includes: (i) preparing core particles comprising a lithium cobalt-based composite oxide; (ii) having an average size (D) in the range of about 3 μm to about 25 μm. 50 Flake graphite was pulverized to prepare a sample with an average size (D) of less than or equal to about 2.5 μm. 50 (iii) Particle-shaped graphite; and (iii) Dry mixing of core particles, particle-shaped graphite and carbon nanotubes to obtain a positive electrode active material.

[0067] According to some exemplary embodiments, a method for preparing positive electrode active materials can be used to form a carbon coating layer comprising carbon nanotubes and graphene having a layered structure ranging from 2 to 50 layers on the surface of core particles. Therefore, positive electrode active materials with high conductivity and particle density can be prepared while reducing or minimizing manufacturing costs, and the adhesion strength and conductivity to the electrode plate can be ensured even when a small amount of binder and conductive material is used during the manufacturing of the positive electrode. Furthermore, as the amount of binder used during the manufacturing of the positive electrode decreases, the amount of positive electrode active material can be increased, allowing the rechargeable lithium battery including the positive electrode active material to exhibit high capacity and high energy density characteristics.

[0068] The following describes in detail the configuration of a method for preparing a positive electrode active material according to some exemplary embodiments.

[0069] (i) Steps for preparing core particles

[0070] Prepare core particles comprising lithium cobalt-based composite oxides. The core particles prepared in step (i) can be described in the same way as the core particles in the positive electrode active material described above, and therefore their detailed description is omitted.

[0071] (ii) Steps for preparing particulate graphite

[0072] The average size (D) will be in the range of approximately 3 μm to approximately 25 μm. 50 Flake graphite was ground to prepare a material with an average size (D) of less than or equal to about 2.5 μm. 50 The particulate graphite prepared in step (ii) has specific physical properties such as average size, thickness, and I. D / I G The values ​​can be described in the same way as the physical properties of the particulate graphite in the above-mentioned positive electrode active material, and therefore their detailed description is omitted.

[0073] The average size (D) of the flake graphite used in step (ii) 50 The size of the flake graphite can be less than or equal to about 20 μm, less than or equal to about 18 μm, less than or equal to about 15 μm, less than or equal to about 12 μm, or less than or equal to about 10 μm, and can be greater than or equal to about 4 μm, greater than or equal to about 5 μm, or greater than or equal to about 6 μm. In this paper, the average size of the flake graphite can be measured by scanning electron microscopy images. In this paper, the average size of the flake graphite (D...) 50 This can be measured by a particle size analyzer, and it means the size of the particles at which the cumulative volume in the particle size distribution is 50% by volume. Alternatively, particle size here can mean the length of the longest axis in a plane perpendicular to the thickness direction in a plate shape.

[0074] Flake graphite may have a Raman spectrum at 1350 cm⁻¹ ranging from about 0.01 to about 0.15, or greater than or equal to 0.01 and less than about 0.15, for example, from about 0.02 to about 0.14, from about 0.08 to about 0.14, or from about 0.1 to about 0.14. -1 Nearby peak intensity (I) D ) at 1580 cm -1 Nearby peak intensity (I) G The ratio of (I) D / I G ).

[0075] In step (ii), the flake graphite can be pulverized using a grinding process. The grinding process can utilize methods known to those skilled in the art, and for example, equipment such as ball mills, bead mills, spray mills, pin mills, roller mills, mixing mills, colloid mills, or air classifying mills (ACMs) can be used.

[0076] In step (ii), the flake graphite can be pulverized by ball milling, using zirconia beads having a size ranging from about 1 mm to about 25 mm, and the milling can be carried out at a speed ranging from about 200 rpm to about 5,000 rpm for about 30 minutes to about 4 hours. The size of the zirconia beads can range from about 1.2 mm to about 23 mm, from about 1.3 mm to about 21 mm, or from about 1.5 mm to about 20 mm. Furthermore, the pulverization of the flake graphite can be carried out at speeds ranging from about 250 rpm to about 4,500 rpm, from about 300 rpm to about 4,000 rpm, from about 400 rpm to about 3,000 rpm, or from about 600 rpm to about 2,000 rpm. Additionally, the pulverization of the flake graphite can be carried out for a duration ranging from about 30 minutes to about 3 hours, or from about 35 minutes to about 3 hours. If the size of the beads, the crushing speed, or the crushing time each meet the above ranges (when the size of the beads, the stirring speed, or the stirring time each meet the above ranges), the particle size of the micro-graphite can be controlled to the desired level.

[0077] (iii) Steps for obtaining positive electrode active material

[0078] Core particles, particulate graphite, and carbon nanotubes are dry-mixed to obtain the positive electrode active material. In step (iii), crystalline carbon derived from particulate graphite is coated onto the surface of the core particles, and a carbon coating layer of graphene with a layered structure ranging from 2 to 50 layers can be formed on the surface of the core particles. Simultaneously, the carbon coating layer formed on the surface of the core particles in step (iii) includes carbon nanotubes. Therefore, the prepared positive electrode active material can have improved conductivity and agglomerate density. Furthermore, because a thin and uniform or substantially uniform carbon coating layer is formed on the surface of the core particles in step (iii), conductivity and adhesion strength to the electrode plate can be ensured even when a small amount of binder is used during the manufacture of the positive electrode. Additionally, as the amount of binder used during the manufacture of the positive electrode decreases, the amount of positive electrode active material can increase, allowing the rechargeable lithium battery to exhibit high capacity and high energy density characteristics. The carbon nanotubes used in step (iii) can be described in the same manner as the carbon nanotubes in the above-described positive electrode active material, and the carbon coating layer formed in step (iii) can be described in the same manner as the carbon coating layer in the above-described positive electrode active material, and therefore its detailed description is omitted.

[0079] Based on the total weight of 100% by weight of core particles, particulate graphite, and carbon nanotubes, particulate graphite can be mixed in amounts ranging from about 0.02% by weight to about 3.0% by weight, for example, from about 0.02% by weight to about 2.8% by weight, from about 0.03% by weight to about 2.5% by weight, from about 0.05% by weight to about 2.0% by weight, from about 0.05% by weight to about 1.0% by weight, from about 0.05% by weight to about 0.5% by weight, or from about 0.05% by weight to about 0.8% by weight. If the mixing amount of particulate graphite meets the above range (when the mixing amount of particulate graphite meets the above range), the high capacity and high energy density characteristics of rechargeable lithium batteries can be improved, while the agglomeration density and conductivity of the positive electrode active material can be improved. For example, even if the amount of particulate graphite is substantially small, less than about 1% by weight (even when the amount of particulate graphite is substantially small, less than about 1% by weight), particulate graphite can be coated on the surface of the core particles as desired, thereby improving the conductivity of the positive electrode active material and increasing the density of the positive electrode.

[0080] Based on the total weight of 100% by weight of core particles, micro-graphite, and carbon nanotubes, carbon nanotubes can be mixed in amounts ranging from about 0.02% by weight to about 3.0% by weight, for example, from about 0.02% by weight to about 2.8% by weight, from about 0.03% by weight to about 2.5% by weight, from about 0.05% by weight to about 2.0% by weight, from about 0.05% by weight to about 1.0% by weight, from about 0.05% by weight to about 0.5% by weight, or from about 0.05% by weight to about 0.8% by weight. If the amount of carbon nanotubes meets the above range (when the amount of carbon nanotubes meets the above range), the aggregate density and conductivity of the positive electrode active material can be ensured, while improving the high capacity and high energy density characteristics of rechargeable lithium batteries. For example, even when the amount of mixed carbon nanotubes is a very small amount less than about 1% by weight (even when the amount of mixed carbon nanotubes is a very small amount less than about 1% by weight), carbon nanotubes can increase the electrical conductivity of the positive electrode active material, increase the aggregate density, and increase the density of the positive electrode.

[0081] Step (iii) can be performed by mixing the core particles, particulate graphite, and carbon nanotubes, and applying a shear force. In this case, while crystalline carbon derived from particulate graphite is disposed in a two-dimensional plane on the surface of the core particles, a carbon coating layer comprising graphene exhibiting a dense crystalline structure can be formed. For example, this process can be performed using equipment for applying shear force, such as equipment with blades inside, but is not limited thereto.

[0082] In step (iii), a mixer such as a Nobilta mixer can be used to mix the core particles, particulate graphite, and carbon nanotubes, and the mixing time can be approximately 1,000 s. -1 From approximately 9,000 s -1 Shear rates within a certain range and blade rotation speeds less than or equal to approximately 20 m / s will mix core particles, microparticles of graphite, and carbon nanotubes.

[0083] Core particles, microparticles of graphite, and carbon nanotubes can be quantized in approximately 1,500 s. -1 From approximately 8,800 s -1 Approximately 2,000 s -1 From approximately 8,800 s -1 Or approximately 2,500 s -1 From approximately 8,500 s -1 Mixing within a range of shear rates. If the range of shear rates meets the above requirements (when the range of shear rates meets the above requirements), a carbon coating layer can be effectively formed on the surface of the core particles while reducing or preventing damage to the core particles.

[0084] The rotational speed of the blades within the device used to apply shear force can be less than or equal to about 18 m / s, less than or equal to about 15 m / s, or less than or equal to about 10 m / s, and greater than or equal to about 3 m / s, greater than or equal to about 4 m / s, or greater than or equal to about 5 m / s. If the rotational speed of the blades meets the above range (when the range of the blade rotational speed meets the above range), a carbon coating layer can be effectively formed on the surface of the core particles while reducing or preventing damage to the core particles.

[0085] Step (iii) can be performed at speeds ranging from about 500 rpm to about 6,000 rpm, and for example, it can be performed at speeds ranging from about 600 rpm to about 5,500 rpm, from about 700 rpm to about 5,000 rpm, or from about 800 rpm to about 4,000 rpm. If the conditions for performing this step meet the above ranges (when the conditions for performing this step meet the above ranges), a carbon coating layer can be effectively formed on the surface of the core particle while reducing or preventing damage to the core particle.

[0086] In step (iii), the core particles, particulate graphite, and carbon nanotubes can be mixed using a dry method (dry mixing). This reduces manufacturing costs and further improves the agglomeration density and conductivity of the positive electrode active material because the carbon coating is formed thinly and uniformly or substantially uniformly. Herein, "dry method" can mean a state where there is no unintentional contact with solvents, such as process solvents, or a state where solvents are not intentionally included. For example, dry mixing can be performed using methods known to those skilled in the art, and, for example, dry mixers (e.g., Norbilta mixers), homogenizers, or Henschel mixers can be used.

[0087] positive electrode

[0088] In some exemplary embodiments, the positive electrode includes a positive electrode current collector and a layer of positive electrode active material on the positive electrode current collector, wherein the positive electrode active material layer includes the aforementioned positive electrode active material. In addition to the aforementioned positive electrode active material, the positive electrode active material layer may further include other types of positive electrode active materials. For example, based on the total weight of 100% of the positive electrode active material layer, the positive electrode active material may be included in amounts ranging from about 60% to about 99.9% by weight, about 70% to about 99.9% by weight, about 80% to about 99.9% by weight, about 90% to about 99.9% by weight, or about 95% to about 99.9% by weight.

[0089] The configuration of the positive electrode according to some example implementations is described in detail below.

[0090] current collector

[0091] There are no particular limitations on the current collector, as long as it is conductive and does not cause adverse chemical changes in the positive electrode and in the rechargeable lithium battery including the positive electrode. For example, the current collector may include a thin film of at least one of the following: aluminum (Al), stainless steel (SUS), indium (In), magnesium (Mg), titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), germanium (Ge), lithium (Li), or combinations thereof, and may include, for example, an aluminum thin film.

[0092] Current collectors can take many forms, such as plates, thin sheets, films, sheets, foils, meshes, porous bodies, foams, or nonwoven materials. For example, current collectors can include microscopic irregularities on their surface, which can improve the adhesion strength to the positive electrode active material.

[0093] The thickness of the current collector can be in the range of about 1 μm to about 20 μm, for example about 5 μm to about 15 μm or about 7 μm to about 10 μm.

[0094] The positive electrode active material layer may further include a binder, a conductive material, or a combination thereof.

[0095] adhesive

[0096] The binder improves the adhesion properties between the active material particles of the positive electrode and with the current collector. For example, the binder may include one or more of, but is not limited to, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers (polymers containing ethylene oxide), polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, epoxy resin, (meth)acrylate resin, polyester resin, and nylon.

[0097] Based on the total weight of 100% by weight of the positive electrode active material layer, the binder may be included in an amount ranging from about 0.1% by weight to about 1% by weight, and for example, less than about 1.0% by weight or less than or equal to about 0.9% by weight.

[0098] conductive materials

[0099] The conductive material is included to provide electrode conductivity, and any electrically conductive material can be used as the conductive material unless it causes an adverse chemical change in the battery. For example, the conductive material may include at least one of carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, carbon nanotube, etc.; metal-based materials including at least one of metal powders or metal fibers such as copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or mixtures thereof.

[0100] Based on the total weight of 100% by weight of the positive electrode active material layer, the conductive material may be included in amounts ranging from about 0% to about 1% by weight, for example from about 0.05% to about 1% by weight, for example less than about 1.0% by weight, less than or equal to about 0.8% by weight, less than or equal to about 0.7% by weight, or less than or equal to about 0.5% by weight. Because the positive electrode active material layer includes the aforementioned positive electrode active material, even if the positive electrode active material layer does not include a separate conductive material or includes a substantially small amount of conductive material (even when the positive electrode active material layer does not include a separate conductive material or includes a substantially small amount of conductive material), it can exhibit desired or improved electronic conductivity, and can exhibit low resistance and high positive electrode density.

[0101] As an example, the density of the positive electrode active material layer can be in the range of about 2.0 g / cc to about 6.0 g / cc, for example, about 2.3 g / cc to about 5.8 g / cc, about 2.5 g / cc to about 5.7 g / cc, or about 2.5 g / cc to about 5.5 g / cc. Alternatively, for example, the density of the positive electrode active material layer can be in the range of about 3.5 g / cc to about 5.0 g / cc, about 3.7 g / cc to about 4.9 g / cc, about 3.8 g / cc to about 4.8 g / cc, or about 4.0 g / cc to about 4.5 g / cc. If the density of the positive electrode active material layer meets the above range (when the density of the positive electrode active material layer meets the above range), the energy density of the rechargeable lithium battery can be improved. For example, because the above-mentioned positive electrode active material has high particle strength and particle surface lubricity, the compression process can be performed at higher pressures. Furthermore, because the surface lubricity of the positive electrode active material is high, the compression efficiency of the positive electrode can be increased through a sliding effect. In addition, because the compression process can be carried out under higher pressure, the pores of the electrode plate in the positive electrode active material layer can be reduced, and the density of the positive electrode active material layer can be further improved.

[0102] The adhesion strength of the positive electrode active material layer to the current collector can be greater than or equal to about 0.5 gf / mm, and the resistivity of the positive electrode active material layer can be less than or equal to about 40 Ω·cm. For example, the adhesion strength of the positive electrode active material layer to the current collector can be greater than or equal to about 1.0 gf / mm, greater than or equal to about 1.5 gf / mm, greater than or equal to about 2.0 gf / mm, or greater than or equal to about 2.5 gf / mm, and can be less than or equal to about 30 gf / mm, less than or equal to about 28 gf / mm, less than or equal to about 25 gf / mm, or less than or equal to about 23 gf / mm. For example, the resistivity of the positive electrode active material layer may be less than or equal to about 35 Ω·cm, less than or equal to about 30 Ω·cm, less than or equal to about 25 Ω·cm, or less than or equal to about 20 Ω·cm, and may be greater than or equal to about 0.5 Ω·cm, greater than or equal to about 1.0 Ω·cm, greater than or equal to about 3.0 Ω·cm, greater than or equal to about 5.0 Ω·cm, or greater than or equal to about 5.5 Ω·cm. For example, because the positive electrode active material layer includes the aforementioned positive electrode active material, even if the positive electrode active material layer does not include a separate conductive material or includes a substantially small amount of conductive material (even when the positive electrode active material layer does not include a separate conductive material or includes a substantially small amount of conductive material), the positive electrode active material layer may exhibit desired or improved electronic conductivity and exhibit low resistance, and even if the positive electrode active material layer includes a substantially small amount of binder (even when the positive electrode active material layer includes a substantially small amount of binder), the positive electrode active material layer may exhibit high adhesion strength to the electrode plate.

[0103] The porosity of the positive electrode can be less than or equal to about 30%, less than or equal to about 25%, or less than or equal to about 20% and greater than or equal to about 1%, greater than or equal to about 5%, or greater than or equal to about 7%. If the porosity of the positive electrode meets the above ranges (when the porosity of the positive electrode meets the above ranges), the capacity and energy density of the positive electrode can be improved. In this paper, the porosity of the positive electrode means the ratio of the volume of pores present within the positive electrode to the total volume of the positive electrode, and can be measured, for example, by mercury porosimetry (mercury porosimetry).

[0104] Rechargeable lithium batteries

[0105] A rechargeable lithium battery according to some exemplary embodiments includes a positive electrode, a negative electrode, and an electrolyte. The positive electrode includes a current collector and a layer of positive electrode active material on the current collector, wherein the layer of positive electrode active material includes the aforementioned positive electrode active material. The rechargeable lithium battery may be a lithium-ion battery using a liquid electrolyte, or an all-solid-state rechargeable battery or a semi-solid-state rechargeable battery using a solid electrolyte. For convenience, the configuration of the lithium-ion battery is described in detail below.

[0106] Depending on their shape, rechargeable lithium batteries can be classified as cylindrical, prismatic, pouch-shaped, coin-shaped, etc. Figures 1 to 4 To illustrate a schematic diagram of a rechargeable lithium battery according to some exemplary embodiments, wherein Figure 1 It is a cylindrical battery. Figure 2 It is a prismatic battery, and Figure 3 and Figure 4 It is a pouch-shaped battery.

[0107] Reference Figures 1 to 4 The rechargeable lithium battery 100 includes an electrode assembly 40 and a housing 50. The electrode assembly 40 has a separator 30 inserted between a positive electrode 10 and a negative electrode 20. The electrode assembly 40 is housed within the housing 50. The positive electrode 10, the negative electrode 20, and the separator 30 may be impregnated with an electrolyte solution (not shown). The rechargeable lithium battery 100 may include, for example, Figure 1 The sealing member 60 of the sealing housing 50 shown. In Figure 2 In this context, the rechargeable lithium battery 100 may include a positive electrode lead connector 11, a positive electrode terminal 12 connected to the positive electrode lead connector 11, a negative electrode lead connector 21, and a negative electrode terminal 22 connected to the negative electrode lead connector 21. For example... Figure 3 and Figure 4 As shown, the rechargeable lithium battery 100 includes Figure 4 The electrode terminals 70 shown in the figure or Figure 3 The positive electrode terminal 71 and negative electrode terminal 72 shown in the figure form an electrical path for leading the current generated in the electrode assembly 40 to the outside of the battery 100.

[0108] Rechargeable lithium batteries according to some exemplary embodiments may be rechargeable at high voltages or suitable for driving at high voltages. For example, the charging voltage of a rechargeable lithium battery may be greater than or equal to about 4.45 V, about 4.45 V to about 4.7 V, about 4.45 V to about 4.6 V, or about 4.45 V to about 4.55 V. By applying the positive electrode active material according to some exemplary embodiments, rechargeable lithium batteries can significantly reduce the amount of gas generated even when charged at high voltages, and can achieve high capacity and long cycle life characteristics.

[0109] negative electrode

[0110] The negative electrode may include a current collector and a layer of negative electrode active material on the current collector. The negative electrode active material layer includes a negative electrode active material and may further include a binder, a conductive material, or a combination thereof.

[0111] Negative electrode active material

[0112] The negative electrode active material may include at least one of the following: a material that can reversibly insert / deintercalate lithium ions, lithium metal, lithium metal alloy, a material capable of doping / dedoping lithium, or a transition metal oxide.

[0113] Materials that can reversibly insert / deintercalate lithium ions may include, for example, crystalline carbon, amorphous carbon, or combinations thereof as active materials for carbon-based negative electrodes. Crystalline carbon may be irregular, or in the form of flakes, scaly, spherical, or fibrous natural or artificial graphite. Amorphous carbon may be or include at least one of soft carbon, hard carbon, mesophase pitch carbonization products, calcined coke, etc.

[0114] Lithium metal alloys include alloys of lithium and metals, wherein the metals include, for example, at least one of the following: Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn.

[0115] Materials capable of doping / dedoping lithium may be, or include, Si-based or Sn-based negative electrode active materials. Si-based negative electrode active materials may include at least one of the following: silicon, silicon-carbon composites, SiO₂, etc. x (0 <x < 2) Si-Q alloy (where Q is or includes at least one of alkali metals, alkaline earth metals, group 13 elements, group 14 elements (excluding Si), group 15 elements, group 16 elements, transition metals, rare earth elements, and combinations thereof, such as Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof) or combinations thereof. The Sn-based negative electrode active material may be or include at least one of the following: Sn, SnO2, Sn alloys, or combinations thereof.

[0116] Silicon-carbon composites can be or include composites of silicon and amorphous carbon. The average particle size (D) of silicon-carbon composite particles... 50 The size can range, for example, from about 0.5 μm to about 20 μm. According to some exemplary embodiments, the silicon-carbon composite can be in the form of silicon particles and amorphous carbon coated on the surface of the silicon particles. For example, the silicon-carbon composite may include secondary particles (cores) in which a primary silicon particle assembly is formed and an amorphous carbon coating (shell) on the surface of the secondary particles. The amorphous carbon may also be present between the primary silicon particles; for example, the primary silicon particles may be coated with amorphous carbon. The secondary particles may be dispersed in an amorphous carbon matrix.

[0117] The silicon-carbon composite may further include crystalline carbon. For example, the silicon-carbon composite may include a core comprising crystalline carbon and silicon particles, and an amorphous carbon coating layer on the surface of the core. The crystalline carbon may be or include artificial graphite, natural graphite, or a combination thereof. The amorphous carbon may include at least one of soft carbon, hard carbon, a mesophase pitch carbonized product, and calcined coke.

[0118] When the silicon-carbon composite includes silicon and amorphous carbon, based on 100 wt% of the silicon-carbon composite, the amount of silicon may be in the range of about 10 wt% to about 50 wt%, and the amount of amorphous carbon may be in the range of about 50 wt% to about 90 wt%. When the silicon-carbon composite includes silicon, amorphous carbon, and crystalline carbon, based on 100 wt% of the silicon-carbon composite, the amount of silicon may be in the range of about 10 wt% to about 50 wt%, the amount of crystalline carbon may be in the range of about 10 wt% to about 70 wt%, and the amount of amorphous carbon may be in the range of about 20 wt% to about 40 wt%.

[0119] For example, the thickness of the amorphous carbon coating layer may be in the range of about 5 nm to about 100 nm. The average particle diameter (D of the silicon particles (primary particles) 50 ) may be in the range of about 10 nm to about 1 μm or about 10 nm to about 200 nm. The silicon particles may be in the form of elemental silicon, a silicon alloy, or an oxidized form. The oxidized form of silicon may be represented by SiO x (0<x≤2). In this case, the atomic content ratio of Si:O indicating the oxidation degree may be in the range of about 99:1 to about 33:67.

[0120] The Si-based negative electrode active material or Sn-based negative electrode active material may be mixed with the carbon-based negative electrode active material. When the Si-based negative electrode active material or Sn-based negative electrode active material is used in combination with the carbon-based negative electrode active material, the weight ratio of the Si-based negative electrode active material or Sn-based negative electrode active material to the carbon-based negative electrode active material may be in the range of about 1:99 to about 90:10.

[0121] Based on 100 wt% of the total weight of the negative electrode active material layer, the negative electrode active material may be included in an amount in the range of about 80 wt% to about 99 wt%, for example, about 85 wt% to about 99 wt% or about 90 wt% to about 99 wt%.

[0122] adhesive

[0123] The binder causes the negative electrode active material particles to adhere to each other, and causes the negative electrode active material to adhere to the current collector. The binder may be or include a non-aqueous binder, an aqueous binder, a dry binder, or a combination thereof.

[0124] Non-aqueous adhesives may include at least one of the following: polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene-propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyimide, or combinations thereof.

[0125] Waterborne adhesives may include at least one of the following: styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinylpyrrolidone, polyepoxygenated alcohol, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, or combinations thereof.

[0126] When an aqueous binder is used as the negative electrode binder, it may further include a cellulose-based compound capable of imparting viscosity. As a cellulose-based compound, one or more of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, or their alkali metal salts may be mixed and used. The alkali metal may be or include at least one of Na, K, or Li.

[0127] Dry adhesives may be or include polymeric materials capable of being converted into fibers, and may be or include at least one of the following: polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or combinations thereof.

[0128] Based on the total weight of 100% by weight of the negative electrode active material layer, the binder may be included in an amount ranging from about 0.5% by weight to about 5% by weight, for example from about 0.5% by weight to about 4% by weight, or from about 1% by weight to about 3% by weight.

[0129] conductive materials

[0130] Conductive materials are included to provide electrode conductivity, and any electrically conductive material can be used as the conductive material unless it causes adverse chemical changes in the battery. Examples of conductive materials include at least one of carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fibers, carbon nanofibers, carbon nanotubes, etc.; metal-based materials including at least one of metal powders or metal fibers such as copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or mixtures thereof.

[0131] Based on the total weight of 100% by weight of the negative electrode active material layer, the conductive material may be included in an amount ranging from about 0.5% by weight to about 5% by weight, for example from about 0.5% by weight to about 4% by weight, or from about 1% by weight to about 3% by weight.

[0132] current collector

[0133] There are no particular restrictions on the negative electrode current collector, as long as it does not cause adverse chemical changes in the negative electrode and the rechargeable lithium battery including the negative electrode. For example, the negative electrode current collector may be or include at least one of the following: copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, polymer substrate coated with a conductive metal, or a combination thereof.

[0134] Negative electrode current collectors can take many forms, such as plates, thin sheets, films, sheets, foils, meshes, porous bodies, foams, or nonwoven materials. For example, negative electrode current collectors can include microscopic irregularities on their surface, which can improve the adhesion strength to the negative electrode active material.

[0135] The thickness of the negative electrode current collector can be in the range of about 1 μm to about 20 μm, for example about 5 μm to about 15 μm or about 7 μm to about 10 μm.

[0136] electrolytes

[0137] For example, the electrolyte used in a rechargeable lithium battery may be or include an electrolyte solution and may include a non-aqueous organic solvent and a lithium salt.

[0138] Non-aqueous organic solvents constitute the medium for transporting ions that participate in the electrochemical reactions of the battery. Non-aqueous organic solvents may be or include at least one of the following: carbonate-based solvents, ester-based solvents, ether-based solvents, ketone-based solvents, alcohol-based solvents, aprotic solvents, or combinations thereof.

[0139] Carbonate solvents may include at least one of the following: dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butyl carbonate (BC), etc.

[0140] Ester solvents may include at least one of the following: methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, decanoic acid lactone, mevalonate lactone, caprolactone, etc.

[0141] Ether solvents may include at least one of the following: dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, tetrahydrofuran, etc.

[0142] Ketone solvents may include cyclohexanone, etc. Alcohol solvents may include ethanol, isopropanol, etc. Aprotic solvents may include at least one of the following: nitriles such as R-CN (where R is a C2 to C20 straight-chain, branched or cyclic hydrocarbon group, and may include double bonds, aromatic rings or ether groups, etc.); amides such as dimethylformamide; dioxolane such as 1,3-dioxolane, 1,4-dioxolane, etc.; sulfolane, etc.

[0143] Non-aqueous organic solvents can be used alone or in mixtures of two or more types of solvents, and when two or more types of solvents are used in mixtures, the mixing ratio can be adjusted as desired to achieve the desired battery performance, as is widely known to those skilled in the art.

[0144] When using carbonate solvents, cyclic carbonates and chain carbonates can be mixed together, and the cyclic carbonates and chain carbonates can be mixed in a volume ratio ranging from about 1:1 to about 1:9.

[0145] Non-aqueous organic solvents may further include aromatic hydrocarbon organic solvents. For example, carbonate solvents and aromatic hydrocarbon organic solvents may be mixed in a volume ratio ranging from about 1:1 to about 30:1.

[0146] The electrolyte solution may further include at least one of vinylene carbonate, vinylene carbonate, or ethylene carbonate compounds to improve battery cycle life.

[0147] Examples of ethylene carbonate compounds may include at least one of the following: fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, and cyanoethylene carbonate.

[0148] Lithium salts dissolved in organic solvents supply lithium ions in batteries, enabling basic operation of rechargeable lithium batteries and improving lithium ion transport between the positive and negative electrodes. Examples of lithium salts may include at least one of the following: LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO2C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), LiC4F9SO3, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2 (where x and y are integers in the range of 1 to 20), lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluorobis(oxalate)phosphate (LiDFBOP), and lithium bis(oxalate)borate (LiBOB).

[0149] The concentration of lithium salt can be in the range of about 0.1 M to about 2.0 M. If the concentration of lithium salt is in the above range (when the concentration of lithium salt is in the above range), the electrolyte solution has the desired ionic conductivity and viscosity, and thus the desired or improved performance can be achieved, and lithium ions can move efficiently.

[0150] diaphragm

[0151] Depending on the type of rechargeable lithium battery, the rechargeable lithium battery may further include a separator between the positive and negative electrodes. The separator may include at least one of the following: polyethylene, polypropylene, polyvinylidene fluoride, or a multilayer membrane of two or more layers thereof, and may be a mixed multilayer membrane such as a polyethylene / polypropylene two-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, a polypropylene / polypropylene / polypropylene three-layer separator, etc.

[0152] The diaphragm may include a porous substrate and a coating, comprising organic materials, inorganic materials or combinations thereof, on one or both surfaces of the porous substrate.

[0153] The porous substrate may be or include a polymer membrane, which is formed from or includes any one or more of the following: polyolefins such as polyethylene and polypropylene, polyesters such as polyethylene terephthalate and polybutylene terephthalate, polyacetal, polyamide, polyimide, polycarbonate, polyetherketone, polyaryletherketone, polyetherimide, polyamideimide, polybenzimidazole, polyethersulfone, polyphenylene ether, cyclic olefin copolymers, polyphenylene sulfide, polyethylene naphthalate, and Teflon (polytetrafluoroethylene), or copolymers or mixtures of two or more thereof. The porous substrate may include glass fiber, or may include a composite membrane of polymer and glass fiber.

[0154] The porous substrate may have a thickness in the range of about 1 μm to about 40 μm, for example about 1 μm to about 30 μm, about 1 μm to about 20 μm, about 5 μm to about 15 μm, or about 10 μm to about 15 μm.

[0155] Organic materials may include (meth)acrylic acid copolymers, which include a first structural unit and a second structural unit, wherein the first structural unit is derived from (meth)acrylamide, and the second structural unit includes at least one structural unit derived from (meth)acrylic acid or (meth)acrylate and a structural unit derived from (meth)acryloylsulfamic acid or a salt thereof.

[0156] Inorganic materials may include inorganic particles, which may include, for example, at least one of the following: Al₂O₃, SiO₂, TiO₂, SnO₂, CeO₂, MgO, NiO, CaO, Ga₂O₃, ZnO, ZrO₂, Y₂O₃, SrTiO₃, BaTiO₃, Mg(OH)₂, boehmite, and combinations thereof, but are not limited thereto. The average particle size (D) of the inorganic particles... 50 The range can be from about 1 nm to about 2000 nm, for example from about 100 nm to about 1000 nm, or from about 100 nm to about 700 nm. In this paper, the average particle size (D) of the inorganic particles is... 50 The particle size distribution can be obtained by randomly selecting about 20 particles from a scanning electron microscope image of inorganic particles, measuring their particle size (diameter, major axis, or major axis length) to obtain the particle size distribution, and then taking the size of the particles with a cumulative volume of 50% of the particle size distribution as the average particle size.

[0157] Organic and inorganic materials can be mixed in a single coating, or a coating comprising organic materials and a coating comprising inorganic materials can be stacked together. The thickness of the coating can range from about 0.5 μm to about 20 μm, for example from about 1 μm to about 10 μm, or from about 1 μm to about 5 μm.

[0158] The rechargeable lithium battery according to some example embodiments may be applicable to, for example, automobiles, mobile phones or various types of electronic devices, but is not limited thereto.

[0159] The following describes embodiments and comparative examples of this disclosure. However, the following embodiments are merely examples of this disclosure, and this disclosure is not limited to the following embodiments.

[0160] Example 1

[0161] (1) Preparation of positive electrode active material

[0162] Preparation of core particles: by using particles with an average particle size of 17 μm (D 50 Large-particle lithium cobalt oxide (LCO, LiCoO2) and an average particle size of 5 μm (D 50 Bimodal core particles were prepared by mixing small lithium cobalt oxide (LCO, LiCoO2) particles in a weight ratio of 7:3.

[0163] Preparation of particulate graphite: Flake graphite (G5 (C-one)) with an average particle size (D) was prepared. 50 ): 3 μm, in Raman spectra at 1350 cm⁻¹ -1 Nearby peak intensity (I) D ) at 1580 cm -1Nearby peak intensity (I) G The ratio of (I) D / I G 0.12) was mixed with ZrO2 beads having a particle size of 2 mm, the ZrO2 beads being 10 times the weight of the flake graphite. The flake graphite was then milled at 1,000 rpm for 1 hour to prepare particulate graphite. At this point, the average particle size (D) of the particulate graphite was... 50 The value is 0.26 μm, and it appears at 1350 cm⁻¹ in the Raman spectrum. -1 Nearby peak intensity (I) D ) at 1580 cm -1 Nearby peak intensity (I) G The ratio of (I) D / I G The value is 0.28.

[0164] To obtain the positive electrode active material: 99.8 wt% of core particles, 0.15 wt% of particulate graphite, and 0.05 wt% of TWCNTs were added to a Norbilta mixer (manufacturer: Hosokawa Co., Ltd.). After adjusting the mixing conditions to 3,000 rpm, the core particles, particulate graphite, and carbon nanotubes were mixed for 10 minutes to obtain the positive electrode active material.

[0165] (2) Manufacturing of the positive electrode

[0166] A positive electrode active material slurry was prepared by dispersing 99.1 wt% of the positive electrode active material prepared in (1), 0.2 wt% of carbon nanotubes as a conductive material, and 0.7 wt% of polyvinylidene fluoride as a binder in N-methylpyrrolidone (NMP) solvent. The positive electrode active material slurry was coated onto a 12 μm thick aluminum substrate (current collector) and dried to form a positive electrode active material layer, which was then compressed to manufacture a positive electrode. In the manufactured positive electrode, the loading level of the positive electrode active material layer was 16 mg / cm². 2 Furthermore, the density of the positive electrode active material layer was 3.38 g / cc. Additionally, SEM analysis of the compressed positive electrode confirmed that the thickness of the positive electrode active material layer was approximately 50 μm.

[0167] (3) Manufacturing of rechargeable lithium battery cells

[0168] The positive electrode and lithium metal counter electrode manufactured in (2) are used, and a separator with a polyethylene-polypropylene multilayer structure is inserted therebetween. A rechargeable lithium battery cell is manufactured by injecting an electrolyte solution prepared by adding 1.3 M LiPF6 lithium salt to a solvent comprising ethylene carbonate, propylene carbonate and propyl propionate mixed in a volume ratio of 10:15:75.

[0169] Example 2

[0170] The positive electrode active material, the positive electrode, and the rechargeable lithium battery cell were manufactured in essentially the same manner as in Example 1, except that: in the process of “(1) Preparation of positive electrode active material” in Example 1, the amount of mixed particulate graphite was changed to 0.1% by weight, and the amount of mixed carbon nanotubes was changed to 0.1% by weight.

[0171] Example 3

[0172] The positive electrode active material, the positive electrode, and the rechargeable lithium battery cell were manufactured in essentially the same manner as in Example 1, except that, in the process of “(1) Preparation of the positive electrode active material” in Example 1, the carbon nanotubes were changed from TWCNT to MWCNT.

[0173] Comparative Example 1

[0174] LiCoO2 (LCO) was prepared as the positive electrode active material for use in the process of “(1) Preparation of positive electrode active material” in Example 1. The prepared positive electrode active material was used to manufacture the positive electrode and the rechargeable lithium battery cell in substantially the same manner as in Example 1.

[0175] Comparative Example 2

[0176] (1) Preparation of positive electrode active material

[0177] Preparation of core particles: by using particles with an average particle size of 17 μm (D 50 Large-particle lithium cobalt oxide (LCO, LiCoO2) and an average particle size of 5 μm (D 50 Bimodal core particles were prepared by mixing small lithium cobalt oxide (LCO, LiCoO2) particles in a weight ratio of 7:3.

[0178] Preparation of particulate graphite: Flake graphite (G5 (C-one)) with an average particle size (D) was prepared. 50 ): 3 μm, in Raman spectra at 1350 cm⁻¹ -1 Nearby peak intensity (I) D ) at 1580 cm -1 Nearby peak intensity (I) G The ratio of (I) D / I G0.12) was mixed with ZrO2 beads having a particle size of 2 mm, the ZrO2 beads being 10 times the weight of the flake graphite. The flake graphite was then milled at 1,000 rpm for 1 hour to prepare particulate graphite. At this point, the average particle size (D) of the particulate graphite was... 50 The value is 0.26 μm, and it appears at 1350 cm⁻¹ in the Raman spectrum. -1 Nearby peak intensity (I) D ) at 1580 cm -1 Nearby peak intensity (I) G The ratio of (I) D / I G The value is 0.28.

[0179] To obtain the positive electrode active material: 99.8% by weight of core particles and 0.2% by weight of particulate graphite were added to a Norbilta mixer (manufacturer: Hosokawa Co., Ltd.). After adjusting the mixing conditions to 3000 rpm, the core particles and particulate graphite were mixed for 10 minutes to obtain the positive electrode active material.

[0180] (2) Manufacturing of positive electrode and rechargeable lithium battery cell

[0181] Using the positive electrode active material of Comparative Example 2 prepared in (1) above, a positive electrode and a rechargeable lithium battery cell were manufactured by a method substantially the same as that in Example 1.

[0182] Comparative Example 3

[0183] (1) Preparation of positive electrode active material

[0184] Preparation of core particles: by using particles with an average particle size of 17 μm (D 50 Large-particle lithium cobalt oxide (LCO, LiCoO2) and an average particle size of 5 μm (D 50 Bimodal core particles were prepared by mixing small lithium cobalt oxide (LCO, LiCoO2) particles in a weight ratio of 7:3.

[0185] Obtaining the positive electrode active material: 99.8 wt% of core particles and 0.2 wt% of TWCNTs were added to a Norbilta mixer (manufacturer: Hosokawa Co., Ltd.). After adjusting the mixing conditions to 3,000 rpm, the core particles and carbon nanotubes were mixed for 10 minutes to obtain the positive electrode active material.

[0186] (2) Manufacturing of positive electrode and rechargeable lithium battery cell

[0187] Using the positive electrode active material of Comparative Example 3 prepared in (1) above, the positive electrode and rechargeable lithium battery cell were manufactured in substantially the same manner as in Example 1.

[0188] Evaluation Example 1: Electron Microscope Image Analysis

[0189] A scanning electron microscope image of the surface of the positive electrode active material manufactured in Example 1 is shown. Figure 5 A transmission electron microscope image of the cross-section of the positive electrode active material manufactured in Example 1 is shown in the figure. Figure 6 middle.

[0190] Reference Figure 5 and 6 The positive electrode active material of Example 1 has a carbon coating layer comprising graphene and carbon nanotubes formed on the surface of the core particle. Furthermore, the carbon coating layer has a film form that continuously surrounds the surface of the core particle. Specifically, in the scanning electron microscope image, the linear portions represent carbon nanotubes, and the black portions represent graphene derived from particulate graphite. That is, a carbon coating layer comprising both graphene and carbon nanotubes is achieved on the surface of the core particle.

[0191] In addition, the cross-section of the positive electrode active material of Example 1 was observed by transmission electron microscopy (TEM). The results confirmed that the carbon coating layer comprises graphene with a layered structure of about 13 layers, and the thickness of the carbon coating layer is from about 3.299 nm to about 5.233 nm.

[0192] Evaluation Example 2: Measurement of the physical properties of the active material of the positive electrode

[0193] The particle density and powder resistance of the positive electrode active materials prepared in the examples and comparative examples were analyzed, and the results are shown in Table 1 below.

[0194] The specific evaluation methods are as follows.

[0195] (1) Particle density

[0196] 3 g of positive electrode active material was placed in a pelletizing mold and held at 9 tons for 30 seconds to produce pellets. The pellet density was calculated using the pellet thickness and weight, as well as the mold diameter.

[0197] (2) Powder resistor

[0198] Using a powder resistance meter (MCP-PD600, Nittoseiko Analytech Co.), 1 g of positive electrode active material was pressurized from 0 kN to 20 kN, and the powder resistance at 20 kN was measured.

[0199] Evaluation Example 3: Performance Analysis of a Rechargeable Lithium-ion Battery Cell

[0200] The energy density of the rechargeable lithium-ion battery cells manufactured in the examples and comparative examples was analyzed, and the results are shown in Table 1 below.

[0201] The specific evaluation methods are as follows.

[0202] After the compressed positive electrode plate was punched (perforated) to a diameter of 14 mm, the thickness and weight were measured to calculate the density of the hybrid layer (positive electrode active material layer). The energy density was then calculated by multiplying the density of the hybrid layer (positive electrode active material layer), the weight fraction of the positive electrode active material, and the initial discharge capacity. In this paper, the initial discharge capacity was measured by subjecting a rechargeable lithium-ion battery cell to initial charge and discharge cycles at 25°C, wherein the cell was charged with a constant current (0.35 C) and a constant voltage (4.56 V, 0.05 C cutoff), and then discharged with a constant current (0.35 C) to 3.0 V.

[0203] Table 1:

[0204]

[0205] Referring to Table 1, for Examples 1 to 3, the particle density was 4.37 g / cm³. 3 Up to 4.39 g / cm 3 The powder resistivity ranges from 1,825 Ω·cm to 2,870 Ω·cm, and the energy density ranges from 785 mAh / cc to 791 mAh / cc.

[0206] Conversely, compared to Examples 1 to 3, in Comparative Example 1 without the carbon coating layer, the particle density was measured to be substantially low, the powder resistance was measured to be substantially high, and the energy density was measured to be substantially low. That is, since the particle density of the positive electrode active material is improved and the powder resistance is reduced by including the carbon coating layer, the electrical conductivity of the positive electrode active material can be improved.

[0207] Furthermore, in Comparative Example 2, where the carbon coating layer comprises only graphene, the particle density was measured to be low, the powder resistance was measured to be high, and the energy density was measured to be low. In Comparative Example 3, where the carbon coating layer comprises only carbon nanotubes, the particle density was measured to be substantially low, the powder resistance was measured to be substantially high, and the energy density was measured to be substantially low. That is, since the carbon coating layer comprises both carbon nanotubes and graphene, the electrical conductivity of the positive electrode active material is improved.

[0208] While this disclosure has been described with respect to exemplary embodiments that are now considered practical, it will be understood that this disclosure is not limited to the disclosed embodiments. Rather, this disclosure is intended to cover various modifications and equivalent arrangements that are included within the spirit and scope of the appended claims.

[0209] Description of reference numerals in the attached figures:

[0210] 100: Rechargeable lithium battery; 10: Positive electrode

[0211] 11: Positive electrode lead connector 12: Positive electrode terminal

[0212] 20: Negative electrode 21: Negative electrode lead connector

[0213] 22: Negative electrode terminal; 30: Diaphragm

[0214] 40: Electrode assembly; 50: Housing

[0215] 60: Sealing component; 70: Electrode terminal piece

[0216] 71: Positive electrode connector; 72: Negative electrode connector

Claims

1. Positive electrode active material, including: Including core particles of lithium cobalt-based composite oxides; and The carbon coating layer on the surface of the core particles, The carbon coating layer includes carbon nanotubes and graphene with a layered structure of 2 to 50 layers.

2. The positive electrode active material according to claim 1, wherein the interlayer spacing d of the layered structure is... 002 In the range of 0.320 nm to 0.350 nm.

3. The positive electrode active material according to claim 1, wherein: The thickness of the graphene is less than or equal to 20 nm; and The graphene has a size of less than or equal to 2.5 μm.

4. The positive electrode active material according to claim 1, wherein the graphene has a Raman spectrum at 1350 cm⁻¹ in the range of 0.15 to 0.

50. -1 Nearby peak intensity I D At 1580 cm -1 Nearby peak intensity I G The ratio I D / I G .

5. The positive electrode active material according to claim 1, wherein the graphene of the carbon coating layer is included in an amount ranging from 0.02% to 3.0% by weight, based on 100% by weight of the total weight of the positive electrode active material.

6. The positive electrode active material according to claim 1, wherein the graphene in the carbon coating layer is derived from an average size D having an average size of less than or equal to 2.5 μm. 50 Microparticle graphite.

7. The positive electrode active material according to claim 1, wherein the carbon nanotubes include one or more of single-walled carbon nanotubes, thin-walled carbon nanotubes, and multi-walled carbon nanotubes.

8. The positive electrode active material according to claim 1, wherein the carbon nanotubes of the carbon coating layer are included in an amount ranging from 0.02% to 3.0% by weight, based on 100% by weight of the total weight of the positive electrode active material.

9. The positive electrode active material according to claim 1, wherein the core particles comprise a lithium-cobalt-based composite oxide represented by chemical formula 1: Chemical Formula 1: Li a1 Co x1 M 1 y1 O 2-b1 X b1 ; in: 0.9≤a1≤1.8, 0.7≤x1≤1, 0≤y1≤0.3, 0.9≤x1+y1≤1.1, and 0≤b1≤0.1; M 1 Including one or more of Al, B, Ba, Ca, Ce, Cr, Cu, Fe, Mg, Mn, Mo, Ni, Se, Si, Sn, Sr, Ti, V, W, Y, Zn, and Zr; and X includes one or more of F, P, and S.

10. The positive electrode active material according to claim 1, wherein the core particles comprise an average particle size D in the range of 8 μm to 20 μm. 50 The first particle and having an average particle size D in the range of 0.5 μm to 6 μm. 50 The second particle.

11. The positive electrode active material according to claim 1, wherein the thickness of the carbon coating layer is in the range of 3 nm to 50 nm.

12. The positive electrode active material according to claim 1, wherein the carbon coating layer is in the form of a film continuously surrounding the surface of the core particle.

13. The positive electrode active material according to claim 1, wherein: The particle density of the positive electrode active material is greater than or equal to 4.35 g / cm³. 3 ;and The powder resistivity of the positive electrode active material is less than or equal to 10,000 Ω·cm.

14. A method for preparing the positive electrode active material according to any one of claims 1 to 13, the method comprising: (i) Prepare core particles comprising lithium cobalt-based composite oxides; (ii) The average size D in the range of 3 μm to 25 μm 50 Flake graphite was pulverized to prepare a material with an average size D of less than or equal to 2.5 μm. 50 Microparticle graphite; and (iii) The core particles, the microparticles of graphite and the carbon nanotubes are dry-mixed to obtain a positive electrode active material.

15. The method for preparing a positive electrode active material according to claim 14, wherein: In the crushing process, the flake graphite is crushed by ball milling, and The ball milling uses zirconia beads with sizes ranging from 1 mm to 25 mm and is carried out at speeds ranging from 200 rpm to 5,000 rpm for durations ranging from 30 minutes to 4 hours.

16. The method for preparing a positive electrode active material according to claim 14, wherein the particulate graphite is mixed in an amount ranging from 0.02% to 3.0% by weight based on the total weight of 100% by weight of the core particles, the particulate graphite, and the carbon nanotubes.

17. The method for preparing a positive electrode active material according to claim 14, wherein the carbon nanotubes are mixed in an amount ranging from 0.02% to 3.0% by weight based on the total weight of 100% by weight of the core particles, the particulate graphite and the carbon nanotubes.

18. The method for preparing a positive electrode active material according to claim 14, wherein: In the dry mixing process, a mixer is used to mix the core particles, the microparticles of graphite, and the carbon nanotubes. The core particles, the microparticles of graphite, and the carbon nanotubes are mixed at a speed ranging from 500 rpm to 6,000 rpm.

19. A rechargeable lithium battery, comprising: Positive electrode, comprising: Current collector, and The positive electrode active material layer on the current collector, The positive electrode active material layer comprises the positive electrode active material according to any one of claims 1 to 13; negative electrode; and Electrolytes.

20. The rechargeable lithium battery according to claim 19, wherein: The positive electrode active material layer further includes a binder and a conductive material; The binder is included in an amount ranging from 0.1% to 1% by weight, based on the total weight of 100% by weight of the positive electrode active material layer; and The conductive material is included in an amount ranging from 0.05% to 1% by weight, based on the total weight of 100% by weight of the positive electrode active material layer.